MANAJEMEN PENYELENGGARAAN PEMBELAJARAN KETRAMPILAN LIFESKILLS ANAK TUNARUNGU DI SEKOLAH LUAR BIASA YAPENAS, CONDONGCATUR, DEPOK, SLEMAN,YOGYAKARTA (JURNAL ILMIAH TUT WURI HANDAYANI, 2013)
The goal of this research was to describe the management implementation of lifeskills teaching, the child after getting lifeskills teaching, supporting factors and inhibitors of lifeskills teaching at Yapenas Special Education, Condongcatur, Depok, Sleman, Yogyakarta.This study used qualitative approach, sources of data were the headmaster, the vice principal student, the vice principal infrastucture, the vice principal staff, teachers who teach lifeskills, and class teachers. The data collection applied were observation, interview, and document. The validation of the data was done by lengthening the participation, perseverance of observation and triangulation.The result of this study showed that the implementation of lifeskills teaching in Yapenas Special Education running well. The result of input evaluation showed that the educators and infrastucture were adequate enaugh, the management of funds from any sources was very good, learning resources were complete. The result of the evaluation process showed that the management of skill programs in lifeskills was good enough, and the teaching process of lifeskills which was involved teaching learning process, student’s interaction and activities in lifeskills teaching was very good. The result of output evaluation showed that the implementation of lifeskills teaching about student’s abillity was very good. The supported factors in the implementation of lifeskills teaching consisted of internal factors such as the strong of student’s motivation and concentration, and the external factors were the good relationship between the school and the student’s parents, the school and goverment, observers of special schools, the availability of infrastucture and funds, and also school cooperation. The obstacles in the implementation of lifeskills teaching come from internal factors such as the deaf student’s tended to be moody, the difficulties in communication, and from the external factors were the limitation of places for practicing lifeskills teaching and the experts in a certain skill for lifeskills teaching.This research concludes the management implementation lifeskills teaching at Yapenas Special Education was arranged and done well. The kinds of skills taught in principle, is quite varied but not enough meet some students who has an aptitude or interest outside deftness lifeskills taught at school. The deftness taught among others: carpentry, food, or cooking sewed or fashion, agriculture and fisheries. Based on conclution of the research should be channeled development of lifeskills taught for students and all the talent capable of facilitated school.